2021
DOI: 10.31958/jsk.v5i1.3188
|View full text |Cite
|
Sign up to set email alerts
|

Dakwah in the Study of Religious Moderation

Abstract: Considering Indonesia as a plural country consisting of various races, ethnicities, religions and languages. So the theme of religious moderation is considered important to be discussed and researched by academics in particular. However, this paper wants to see how the Messenger of Allah actualized the context of religious moderation in his da'wah, either da'wah in Mecca or da'wah in Medina. The results of this study indicate that the Prophet succeeded in practicing the concept of religious moderation both whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…Preaching is an activity of conveying God's message, and therefore a very noble job. Therefore, preaching must be delivered in a good way (bil hikmah) so that good intentions are not counter-productive (Hasanah, 2021). The Qur'an has several signs for conveying messages through language by using the word qoulan (meaning words), which is juxtaposed with the words layyina (meaning gentle, that preaching must be conveyed in a gentle way).…”
Section: The Role Of Language and Communication In Da'wahmentioning
confidence: 99%
“…Preaching is an activity of conveying God's message, and therefore a very noble job. Therefore, preaching must be delivered in a good way (bil hikmah) so that good intentions are not counter-productive (Hasanah, 2021). The Qur'an has several signs for conveying messages through language by using the word qoulan (meaning words), which is juxtaposed with the words layyina (meaning gentle, that preaching must be conveyed in a gentle way).…”
Section: The Role Of Language and Communication In Da'wahmentioning
confidence: 99%
“…Da'wah in Indonesia between studies that are academic in nature and the reality of da'wah in society has not shown a functional synergistic relationship (Hasanah, 2021).…”
Section: Theoretical Studymentioning
confidence: 99%
“…In fact, da'wah can also be used as propaganda or a moment to influence others. Da'wah is an attempt to convey something to others, both to individuals and groups about the view of human life according to Islam (Hasanah 2021). Meanwhile, according to Asman et al, da'wah is an effort to improve a new civilization for humans (Fathurrrahman et al 2021).…”
Section: Reflections On the Interpretation Of Da'wah Verses: From Con...mentioning
confidence: 99%